2011
DOI: 10.4028/www.scientific.net/amr.243-249.3599
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Analysis of Shallow Tunnel Excavation

Abstract: In this paper, FLAC3D, the general software for geotechnical engineering project, is used to conduct two-dimensional numerical simulation for typical shallow tunnel excavation methods which include full-section method, the upper and lower step method, three-step method and CRD method etc.Effects of different excavation methods to the stability of tunnel surrounding rock are analyzed. The paper selected a subsistent tunnel as the research object. With construction simulation of different excavation methods, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Up to now, many research workers who major in the tunnel project bring a large number of mathematical analysis methods into the analysis of the stability of the slope such as block limit equilibrium method imbalance thrust method, Principle of red flat projection analysis (Jin, Cui, & Lu, 2000;Xiao, 2001;Yang & Cheng, 2002). Along with the development of computer technology, the researchers also bring the simulation research into the field (Tang, Wang, & Li, 2011;Zhang, Lou, Huang, Liu, & Yang, 2011;Zhao, Shao, & Hang, 2009). A preliminary study of the engineering stability of the Shilou tunnel in the Hipparion red clay were studied by the establishing of finite element numerical model (Peng, Ma, Wang, & Xie, 2013;Wang, Gao, Quan, & Qin, 2014;Wang & Wang, 2009;Wang, Xia, & Gu, 2013;Xie & Wang, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many research workers who major in the tunnel project bring a large number of mathematical analysis methods into the analysis of the stability of the slope such as block limit equilibrium method imbalance thrust method, Principle of red flat projection analysis (Jin, Cui, & Lu, 2000;Xiao, 2001;Yang & Cheng, 2002). Along with the development of computer technology, the researchers also bring the simulation research into the field (Tang, Wang, & Li, 2011;Zhang, Lou, Huang, Liu, & Yang, 2011;Zhao, Shao, & Hang, 2009). A preliminary study of the engineering stability of the Shilou tunnel in the Hipparion red clay were studied by the establishing of finite element numerical model (Peng, Ma, Wang, & Xie, 2013;Wang, Gao, Quan, & Qin, 2014;Wang & Wang, 2009;Wang, Xia, & Gu, 2013;Xie & Wang, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vardakos et al 11 used Universal Distinct Element Code (UDEC) software to carry out numerical analysis for Shimizu large-section tunnel in Japan, verifying the mechanical construction effect of ''TBM heading excavation method,'' and they studied the law of surface subsidence at the same time. By the step method, full section method, and CRD method in the excavation of soft rock tunnel, Zhao et al 12 adopted FLAC3D to simulate the stress of the surrounding rock in the process of construction, and the results showed that the excavation based on CRD method had a good controlling effect on the displacement of surrounding rock. With the engineering background of Chongqing Rail Transit Line No.…”
Section: Introductionmentioning
confidence: 99%